1991
DOI: 10.3109/00207459108987188
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Associated Autoimmune Features in Heroin Addicts: Correlation to HIV Infection and Dementia

Abstract: We report here on brain associated autoimmune features in opiate-dependent subjects. This study includes 107 (37 HIV + and 70 HIV -) hospitalized heroin-addicted subjects on a methadone maintenance program, and 45 healthy individuals. Human brain S100 protein, neuron specific enolase (NSE), myelin basic protein (MBF), and old tuberculin (OT) were used as antigens in the study. Serum autoantibodies to brain antigens S100, NSE and MBP were detected by ELISA, whereas delayed hypersensitivity skin reactions were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Some studies have found that recreational drugs such as cocaine, amphetamines, marijuana, and heroin, acting as environmental toxins, may stress and injury immune stem cells and engender subsequent autoimmune disease development and progression. 37,38 Older age and female sex were independent predictors for autoimmune connective tissue disease in this study. Using participants <20 years old as references, we found the risk of autoimmune connective tissue disease increased with age (AHR = 1.7 in age 20-34 years, AHR = 2.9 in age 35-49 years, AHR = 4.3 in age 50-64 years, and AHR = 5.0 in age ≥65 years).…”
Section: Discussionsupporting
confidence: 54%
“…Some studies have found that recreational drugs such as cocaine, amphetamines, marijuana, and heroin, acting as environmental toxins, may stress and injury immune stem cells and engender subsequent autoimmune disease development and progression. 37,38 Older age and female sex were independent predictors for autoimmune connective tissue disease in this study. Using participants <20 years old as references, we found the risk of autoimmune connective tissue disease increased with age (AHR = 1.7 in age 20-34 years, AHR = 2.9 in age 35-49 years, AHR = 4.3 in age 50-64 years, and AHR = 5.0 in age ≥65 years).…”
Section: Discussionsupporting
confidence: 54%
“…Autoimmune hearing losses, however, are variable and have been described as having sudden or rapid onset, unilateral or bilateral presentation, transient or permanent pathology, and both cochlear and neural sites of lesion (Cadoni et al, 2002;Bovo et al, 2006). Hearing Loss from Speedballing/Fowler & King Autoimmune circulatory and brain-related pathologies resulting from the abuse of both cocaine and heroin have been noted (Savona et al, 1985;Jankovic et al, 1991). Hence, an autoimmune reaction cannot be eliminated as a possible mechanism for the bilateral hearing loss in the present case.…”
Section: Discussionmentioning
confidence: 99%